Chemical Dopant‐Free Doping by Annealing and Electron Beam Irradiation on 2D Materials. (2nd July 2021) - Choi, Min Sup; Lee, Myeongjin; Ngo, Tien Dat; Hone, James; Yoo, Won Jong
Abstract: Doping is a key technique for forming complementary metal‐oxide‐semiconductor (CMOS) that is a basic building block for current state‐of‐the‐art semiconductor devices. However, conventional doping methods such as ion implantation are unsuitable for 2D materials due to their ultra‐thinness to accommodate substitutionally doped atomic structures and vulnerability to high energy ion bombardment. Chemical doping methods have been widely used for 2D materials to induce a charge exchange transfer; however, they are subjected to surface contamination which can be detrimental for high quality semiconductor device processing. In this work, the authors reveal the effects of chemicals‐free doping in which annealing induces a p‐doping effect by physisorption and substitution of oxygen atoms while electron beam irradiation selectively n‐dopes MoTe2, based on the results obtained by electrical characterization and Kelvin probe force microscopy. The annealing increases work‐function of MoTe2 which undergoes oxidation as observed in the reduction of surface potential and the transition of transfer curves toward the p‐type behavior. Electrical measurements and a significant reduction in surface potential after electron beam irradiation indicate the generation of trapped charges which is responsible for the n‐doping effect. Subsequently, the authors fabricate a CMOS inverter consisting of distinctively p‐ and n‐doped areas of MoTe2 . Abstract : In this work, chemical‐free and clean doping methods for 2D semiconducting materials are developed. The p‐ and n‐doping in MoTe2 field‐effect transistors are induced by annealing and e‐beam irradiation, attributed to work‐function modification via absorption of oxygen molecules and charge trapping at interfaces, respectively.